(3EQZGe ChdjGA GdTjWGf HPcQ efGbH ChdjGA GdQMefs - (3eMeO YHO GdQDha Hf JGL GdYGQajf GHf Ydj Hf Rjf GdYGHOjf GdMOGOj Ke GdefGhj GdbGgQj, Rjf GdOjf,J (B1031 (3g` s ((3eMeO Hf LeGd GdOjf GdCfUGQi GdeJHhdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY GdPjf ChJhG GdYde OQLGJ CUajGA hChdjGAg ai CQaY GdWHbGJ GdN s
(3BNQgG (B:s
(3QVi Gddg Yfg hYf SGFQ GdChdjGA hGdUGdMjf hCgd WGYJg CLeYjf ef Cgd GdSehGJ hCgd GdCQVjf hUdi Gddg Ydi SjOfG eMeO NGJe GdCfHjGA hGdeQSdjf s
(3Cdag HYO Cf aQZ ef cJGH GdWHbGJ GdcHQi GdeSei GdchGcH GdOQjI ai efGbH GdSGOI GdUhajIs
(3hGdejcQhajde Hg Jda HSjWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B220s
Keywords: (3GdJGQjNs